Production of Long Chain Fatty Alcohols Found in Bumblebee Pheromones by Yarrowia lipolytica - Hambalko, Jaroslav; Gajdoš, Peter; Nicaud, Jean-Marc; Ledesma-Amaro, Rodrigo; Tupec, Michal; Pichová, Iva; Čertík, Milan (Frontiers in Bioengineering and Biotechnology, 2021)
Fatty alcohols (FA-OH) are aliphatic unbranched primary alcohols with a chain of four or more carbon atoms. Besides potential industrial applications, fatty alcohols have important biological functions as well. In nature, fatty alcohols are produced as a part of a mixture of pheromones in several insect species, such as moth, termites, bees, wasps, etc. In addition, FA-OHs have a potential for agricultural applications, for example, they may be used as a suitable substitute for commercial insecticides. The insecticides have several drawbacks associated with their preparation, and they exert a negative impact on the environment. Currently, pheromone components are prepared mainly through the catalytic hydrogenation of plant oils and petrochemicals, which is an unsustainable, ecologically unfriendly, and highly expensive process. The biotechnological production of the pheromone components using engineered microbial strains and through the expression of the enzymes participating in the biosynthesis of these components is a promising approach that ensures ecological sustenance as well. The present study was aimed at evaluating the production of FA-OHs in the oleaginous yeast, Yarrowia lipolytica, with different lengths of fatty-acyl chains by expressing the fatty acyl-CoA reductase (FAR) BlapFAR4 from B. lapidarius, producing C16:0-OH, C16:1∆9-OH, and lower quantities of both C14:0-OH and C18:1∆9-OH, and BlucFAR1 from B. lucorum, producing FA-OHs with a chain length of 18–26 carbon atoms, in this yeast. Among the different novel Y. lipolytica strains used in the present study, the best results were obtained with JMY7086, which carried several lipid metabolism modifications and expressed the BlucFAR1 gene under the control of a strong constitutive promoter 8UAS-pTEF. JMY7086 produced only saturated fatty alcohols with chain lengths from 18 to 24 carbon atoms. The highest titer and accumulation achieved were 166.6 mg/L and 15.6 mg/g DCW of fatty alcohols, respectively. Unlike JMY7086, the BlapFAR4-expressing strain JMY7090 produced only 16 carbon atom-long FA-OHs with a titer of 14.6 mg/L.